IDENTIFYING DRUG COMPOUNDS TARGETING TUMOR METABOLISM IN GLIOBLASTOMAS - Zadeh, Gelareh (Oxford University Press, 2014)
BACKGROUND: Rapidly proliferating tumour cells preferentially use aerobic glycolysis over oxidative phosphorylation (OXPHOS) to support growth and survive unfavorable microenvironment conditions. This metabolic reprogramming is referred to as the “Warburg effect”. We have shown that glycolytic enzyme hexokinase 2 (HK2) is crucial for the Warburg effect in human glioblastoma multiforme (GBM). We also demonstrate that loss of HK2 sensitizes GBM cells in-vitro and in-vivo to chemo and radiation therapy, significantly prolonging survival in intracranial models. We also show that loss of HK2 is most relevant in hypoxia. Given these results and that HK2 is an enzyme with little to no expression in normal brain, it provides an attractive target for targeting in GBMs. However, no direct inhibitor of HK2 that crosses the blood brain barrier exists. We therefore explored whether a system biology approach to identify gene networks regulated by or associated with HK2 that could lead to promising treatment strategies. METHODS: Using HK2 knockdown by siRNA in established GBM cell lines and primary GBM cultures we established gene signatures and networks associated with HK2 expression, identifying 1000 genes with a 2 fold change with p-value <0.01 and false discovery rate of <1%. Using a drug screen of 30 compounds that were predicted to repress HK2 expression and associated metabolic gene signatures we identified the azole class of antifungals as inhibitors of tumour metabolism by reducing proliferation, lactate production, glucose uptake and increasing O2 consumption in GBM cells but not primary normal human astrocytes or normal neural stem cells. RESULTS: We evaluated the in vivo efficacy of these azole compounds in pre-clinical orthotopic xenograft mouse models and transgenic models of GBM. The compounds in combination with standard chemo and radiation therapy significantly restrict tumor growth, alter tumor hypoxia and ROS production. We also show that there is a altered response to DNA damage pathways using these compounds, suggesting novel metabolic mechanisms by which these antifungals sensitize GBMs to treatment. CONCLUSIONS: The azole class of antifungals may represent a new way of targeting tumour metabolism in tumours dependent on HK2. SECONDARY CATEGORY: Tumor Biology.